Analisis Sebaran Spasial Gelandangan dan Pengemis - Nur Hasanah; Laode Muhamad Irsan; Rahma Musyawarah; Amniar Ati; Septianto Aldiansyah; Tahir (Jurnal Penelitian Pendidikan Geografi, 2024)
Kendari City is the capital of Southeast Sulawesi province which is the center of industrial, trade, and service activities for its people. This is an attraction for immigrants from outside the area to come to live or look for work. The development of cities invites migration flows from villages to cities, population mobility and the attraction of city income result in village residents coming to cities which is caused by poverty, giving rise to homeless people and beggars in urban areas. This research aims to analyze the spatial distribution of homeless and beggars in the Kendari Bay area and create a route map for homeless and beggars in the Kendari Bay area. The research method used is survey research with a spatial approach using a geographic information system application. Based on the research results, it was found that the distribution of homeless and beggar locations was spread across several points, namely tourist areas, places of worship, and elite residential areas. Meanwhile, the movement route for homeless beggars in the city of Kendari is in the Citra Land road area towards the Al-Alam mosque, the Kendari Beach Route, the Kendari Bay Platform, and the Bahteramas Bridge.